1992
DOI: 10.1105/tpc.4.2.225
|View full text |Cite
|
Sign up to set email alerts
|

A maize ribosome-inactivating protein is controlled by the transcriptional activator Opaque-2.

Abstract: Although synthesis of the cytosolic maize albumin b-32 had been shown to be controlled by the Opaque-2 regulatory locus, its function was unknown. We show here that b-32 is a member of the large and widely distributed class of toxic plant proteins with ribosome-inactivating activity. These ribosome-inactivating proteins (RIPs) are RNA N-glycosidases that remove a single base from a conserved 28s rRNA loop required for elongation factor l u binding. Cell-free in vitro translation extracts were used to show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
5

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 54 publications
4
76
0
5
Order By: Relevance
“…In common with all characterized plant RIP the toxicity of this JIP60 derivative is associated with depurination of reticuIocyte 28S rRNA (Bass et al, 1992;May et al, 1989). Like the Type I endosperm RIP, JIP60 and derivatives do not significantly affect translation by wheat germ extract, suggesting that JIP60 is not toxic to plant cells (Stirpe and Hughes, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In common with all characterized plant RIP the toxicity of this JIP60 derivative is associated with depurination of reticuIocyte 28S rRNA (Bass et al, 1992;May et al, 1989). Like the Type I endosperm RIP, JIP60 and derivatives do not significantly affect translation by wheat germ extract, suggesting that JIP60 is not toxic to plant cells (Stirpe and Hughes, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…First, JIP60 and maize RIP differ from the Type I and II RIP in containing extra, internal peptides of 20-25 amino acids. Removal of this linker peptide is required for activation of one of the maize RIPs (Bass et al, 1992;Walsh eta/., 1991). Second, JIP60 and ricin differ from the maize and Type I RIP in containing large C-terminal regions.…”
Section: Confirmation Of the Jip60 Open Reading Frame And Sequence Homentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that O2 regulates more genes than just the 22-kDa α-and β-zeins (39,40). Furthermore, the QPM phenotype comprises several QTLs, which make quantitative contributions (24).…”
Section: Scanning Electron Microscopy Of Endosperm From γRnai In Qpmmentioning
confidence: 99%
“…The N-terminal half of JIP60 is related to both type I and type II RIPs, such as the Mirabilisjalapa antiviral protein (Habuka et al, 1989), saporin-6 from Saponaria officinalis (Benatti et al, 1989), and ricin from Ricinuscommunis (Lambet al, 1985) (see Reinbothe et al, 1994, for comparison). Whereas type I RlPs are basic proteins that consist of a single polypeptide chain of 25 to 32 kD (for references, see Bass et al, 1992), type II RlPs contain, in addition to the N-terminal RIP domain, a second domain that confers lectinlike properties to these proteins Pihl, 1973, 1982). 60th types of RIP are exceptionally potent inhibitors of eukaryotic protein synthesis (Coleman and Roberts, 1982;Stirpe et al, 1988).…”
Section: General Depression Of Translation: Jip60 Lnactivates Proteinmentioning
confidence: 99%